Pengaruh Pengendalian Intern Terhadap Piutang Tak Tertagih - Annisa Rafika Faradilla; Eva Najmiyatul Lailiyah; Salma Salsabilla; Jumaiyah Jumaiyah (Accounting Study Program, Faculty of Economics and Business, 2021)
Internal control is an action taken by the company in regulating the company's activities so that the goals set are achieved. The key to the success of the company's activities is to carry out good internal control. One of them is internal control on accounts receivable. The purpose of writing this article is to anticipate the possibility of bad debts. This article describes how to implement internal control of accounts receivable to minimize bad debts in a company. The method used in the preparation of this article is a literature study by looking for references that are relevant to the problem. Based on the results of the literature study, it shows that good internal control of accounts receivable can minimize bad debts.